2015
DOI: 10.1016/j.jclepro.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Improved yield and higher heating value of biochar from oil palm biomass at low retention time under self-sustained carbonization

Abstract: a b s t r a c tOil palm biochar with high yield and higher heating value under low energy requirement is required for improved waste management and utilization in the palm oil industry. This paper presents, a selfsustained carbonization of oil palm empty fruit bunch biomass, without internal heating element, which produced high biochar yield and higher heating value. Three different particle sizes of pressedshredded oil palm empty fruit bunch biomass, i.e. below 29 mm, 30e99 mm and 100e150 mm, at 8 e10% moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 17 publications
4
16
2
Order By: Relevance
“…Despite the lower costs of this technology, the quality of the product produced was as good as those produced using the high‐end technology. Based on the results, 26 wt% of the biocharcoal yield was obtained with a calorific content of 25 MJ kg −1 , which was higher than conventional charcoal …”
Section: Emerging Technologies For Renewable Materials Production Fromentioning
confidence: 99%
“…Despite the lower costs of this technology, the quality of the product produced was as good as those produced using the high‐end technology. Based on the results, 26 wt% of the biocharcoal yield was obtained with a calorific content of 25 MJ kg −1 , which was higher than conventional charcoal …”
Section: Emerging Technologies For Renewable Materials Production Fromentioning
confidence: 99%
“…According to the proposed circular plan of agricultural waste utilization, plant residues, animal manures, and food wastes are recycled to produce engineered biochar are specifically designed for treating the wastewater generated from agricultural and domestic sources. At the same time, biochar can be applied to agricultural fields as a soil amendment to improve WUE [136], remediate diffuse-source contamination [137], and/or improve crop yields [48]; it can also be used as a clean fuel for energy supply (heading value >23 MJ/kg) [138,139]. It has been reported that the addition of biochar to soil could often enhance the plant available water (PAW) and WUE, although the soil type played an important role on the influence [140].…”
Section: Multidimensional Benefits In Circular Agriculturementioning
confidence: 99%
“…While the dry weight of oil palm empty fruit bunches contains organic matter consisting of N 0.8%, P 0.1-0.7%, K 2.4-2.8% and Mg 0.2-0.8. The chemical composition of oil palm biomass fuels has also been described in [42][43][44][45]. The characteristics of palm oil biomass fuel is a very important one and also affects the combustion performance.…”
Section: Properties Of Opbcmentioning
confidence: 99%